Sixty-one years later: a second species of Scolebythus Evans (Hymenoptera: Scolebythidae) from southern Madagascar - Brazidec, Manuel (Zootaxa, 2024)
Despite recent advances in the systematics and taxonomy of the relictual family Scolebythidae, the type genus Scolebythus Evans, 1963 remained monospecific for more than sixty years. Here, I describe and illustrate Scolebythus bekilyensis sp. nov. from a female specimen collected in southern Madagascar. This discovery emphasizes on the endemism of this genus, which is unique within the Scolebythidae for being restricted to one biogeographic realm, and suggests that potential new species are yet to be discovered in this megadiverse region.